Evaluation of reproductive profile in male albino rats following varied duration of administration with Revive capsule - Ibama, Onengiyeofori; Green, Kinikanwo I.; Nwachuku, Edna O.; Onwuli, Donatus O.; Ben-Chioma, Adline Erinma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Revive capsule is a polyherbal formulation commonly used to treat erectile dysfunction or enhance libido in men. Some of the individual herbs used in the formulation of this drug have been known scientifically to affect various biochemical components of the human body; hence this study was aimed at evaluating the reproductive profile in male albino rats following varied duration of administration with Revive capsule. Methods: A total of 42 male albino rats were used for the study, and were divided into six (6) groups of seven (7) rats each. They were allowed to acclimatize for two (2) weeks by maintaining 12-hour light and dark cycles daily, with access to standard feed and water ad libitum. Group A (negative control) rats were administered with distilled water once daily, while groups B, C, D, E and F were administered once daily with 72 mg/kg of Revive capsule for 1 week, 2 weeks, 3 weeks, 4 weeks and 6 weeks respectively. The rat dose administered was extrapolated from the human dose using the formula by Paget and Barnes. At the end of each treatment week, the rats were allowed to fast overnight, followed by their anaesthetization using chloroform, and blood sample collection via jugular vein puncture. Also, the testes were excised; the epididymis were also excised from the testes and used immediately for semen analysis, while the epididymis-free testes were examined histologically. Rat-specific test kits with ELISA method were used to analyze serum LH, FSH and testosterone. Results: The results showed a significant increase (p<0.05) in serum LH, FSH and testosterone levels, and a significant increase in sperm count and sperm quality parameters in the treatment groups compared to the negative control, with the maximum levels attained after 6 weeks of treatment (group F). Also, photomicrographs of histologically examined testes of the treatment groups appeared indifferent from those of the negative control. Conclusions: These findings may suggest that in using a rat model, treatment with Revive capsule at the appropriate dosage for 6 weeks is safe, and that, besides its acclaimed use in enhancing libido or treating erectile dysfunction, it may also be effective in promoting male fertility.